Polymorphism of innate immunity receptor genes in newborns with hypoxic-ischemic brain damage - L. Yu. Barycheva; A. S. Idrisova; E. S. Kuzmina; K. S. Mezhidov (Аллергология и Иммунология в Педиатрии)
.